A Structured Social Media Health Support Program after Bariatric Surgery - Tamir, Orly; Kais, Hassan; Accos-Carmel, Moran; Kolobov, Tatyana; Matthews, Gideon; Lipsits, Aviva; Shalev, Yuval; Sheffer-Benton, Sigal; Benis, Arriel (Applied Clinical Informatics, 2024)
Background Social media networks have been found to provide emotional, instrumental, and social support, which may contribute to improved adherence to postbariatric surgery care recommendations.Objectives This study aimed to evaluate the impact of an online social media-based, health care professional-led, educational and support program on patients' long-term engagement with and adherence to follow-up guidelines, self-care recommendations, and weight management after bariatric surgery.Methods An observational cohort study, employing mixed methods, accompanied a 12-week interactive, structured, social media psychoeducational intervention program delivered on Facebook. Program participants, who had undergone one bariatric surgery within the past 1 to 7 years and were at least 18 years old at the time of surgery, were invited to join the program via posts online. Interested individuals were provided information about the program and the accompanying evaluation study, and those who met requirements completed study questionnaires before and after the program. Questionnaires included demographic and anthropometric information; postoperative recommendations received and their clarity and implementation; attitudes toward recommendation adherence; and well-being. Daily system data on program engagement were collected from the Facebook website.Results Of the 214 participants enrolled in the program, 101 (80.2% female, mean age 43.8 ± 9.1 years and mean body mass index 30.2 ± 6.8 kg/m2, 1–7 years after bariatric surgery) completed both baseline and end-of-program questionnaires and were included in the analysis. Following the program, improvements were observed in most aspects of participants' adherence to postoperative recommendations and well-being. Close to half of the participants (44.6%) reported reaching their postoperative target weight at the end of the program or maintaining it throughout the program. Video posts drew higher participant engagement than other media, and content about proteins received the highest number of reactions. However, participants' active engagement gradually declined over time.Conclusion Interactive health support on social media can positively enhance patient engagement, adherence to treatment recommendations, health outcomes, and overall well-being.
Keywords: social media; customer health informatics; continuity of care; patients with chronic illness; social networking; internet-based program; bariatric surgery; obesity